2012
DOI: 10.1007/s12529-012-9235-4
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Sexual Risk Behavior Among High-Risk Couples in Northern India

Abstract: Purpose This study sought to assess the feasibility of conducting a group, culturally tailored behavioral intervention and its impact on sexual barrier use, self efficacy, knowledge, conflict resolution and coping among high risk heterosexual couples in Northern India. Method This pilot study was conducted at the Post Graduate Institute of Medical Education and Research (PGIMER), Chandigarh, India from February 2008 to January 2009. Thirty sexually active high risk couples were drawn from a convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…A study by Jones et al . [22] had illustrated the positive effect of group cognitive behavior intervention strategy to change inconsistent condom use to consistent use and also the enhancement in self-efficacy and improvement in communication among high-risk sex couples in India.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jones et al . [22] had illustrated the positive effect of group cognitive behavior intervention strategy to change inconsistent condom use to consistent use and also the enhancement in self-efficacy and improvement in communication among high-risk sex couples in India.…”
Section: Discussionmentioning
confidence: 99%
“…A study in South Africa, found that many women who get pregnant before marriage do so to prove their motherhood to their prospective future husbands so as to gain acceptance and approval (White et al 1990). Additionally, women engage in unprotected sex to show love and view such sex as an important means of increasing their connectedness with their partners (Jones et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is limited awareness surrounding issues of STIs, and knowledge about STIs other than HIV is low ( 41 , 42 ). Gender inequality is similarly a compounding factor for both risk and perceived risk of contracting an STI among married women ( 43 , 44 ). Lack of knowledge of sexual and reproductive health issues among men has also been put forward ( 45 ).…”
Section: Current Initiatives and Barriers To Chlamydia Tracmentioning
confidence: 99%